Effects of nitroglycerine on coronary flow velocity before and during adenosine provocation. Issue 1 (December 2016) - Wittfeldt, Ann; Jeppsson, Anders; Gan, Li-Ming
Abstract Background Transthoracic echocardiography-assessed coronary flow velocity reserve (CFVR) evaluates coronary microvascular arterial function. Coronary flow velocity measurements at baseline and during hyperemia are used to calculate CFVR. Adenosine infusion induces hyperemia but it is not known if it causes a maximal response. We hypothesized that pre-treatment with nitroglycerine before adenosine provocation enhances hyperemia. Methods Twenty-three healthy study subjects (mean age 27.5 ± 5.5, 35% women) underwent CFVR measurements before and after pretreatment with sublingual nitroglycerine (0.5 mg). Hyperemia was induced by adenosine infusion (140 μg/kg/min). In addition, the effect of nitroglycerin on left main coronary artery diameter was assessed. Results Pretreatment with nitroglycerine increased median CFVR from 3.6 (range 2.8–4.3) to 5.0 (4.1–6.0), p  = 0.002. The increase was caused by a marked reduction in baseline coronary flow velocity 17 (15–24) vs 27 (19–31) cm/s, p  < 0.0001) while hyperemic velocity remained unchanged (90 (68–116) vs 93 (75–105) cm/s, p  = 0.48). Nitroglycerin significantly dilated the left main coronary artery (from median 3.1 (2.7–3.6) mm to 3.8 (3.1–4.3) mm, p  = 0.018). Conclusion Pretreatment with nitroglycerine dilates coronary arteries and increases coronary flow velocity reserve indicating that adenosine alone causes a submaximal hyperemia.